PENGARUH TINGKAT PENDIDIKAN, PENGALAMAN & ORIENTASI STRATEGI SERTA PENGEMBANGAN STRATEGI INDUSTRI MIKRO (MIKRO) (SEBUAH TINJAUAN TEORI) - Djatmiko, Andreas Andre (STKIP PGRI TULUNGAGUNG, 2013)
Intention of this research is to test by normative/theory among education level, experience, and strategy orientation conducted by owner an industry, specially micro industry, and also development of conducted strategy to performa of effort either through partial and also by simultan. Which this research background is business environment which progressively complex, claiming the effort which pertained middle and micro have to can develop x'self in order to winning emulation and can stay, grow, and expand better. At middle and micro effort most made by strategic development of owner at the same time manager. Influence of owner at business strategy stronger than with effort with larger ones scale. This matter is caused by owner have strong ability in passing challenge and in striving election of business strategy to reach successfulness of effort him. Development of effort basically can be done with three way of, that is : by developing new market by extending from local market or a market of regional to national market or is international. Second: is by innovate product by creating new product for cutomer which have there is now and also to come. Thirdly: concerning development of network of effort and relation/link. It’s implication for middle and micro industry with same job/activity/colaboration with cutomer, suplier, distributor, other organization and competitor. Relation between variable of dependen that is performa of effort and independent variable of him can be yielded by using analyzer of regresi doubled. From result of research known that education storey;level, experience of strategy orientation and owner and also development of strategy have an effect on to performa of effort. While factor having influence most dominant to performa variable development of strategy.